Hunters and Gatherers of Pictures: Why Photography Has Become a Human Universal - Kislinger, Leopold; Kotrschal, Kurt (Frontiers in Psychology, 2021)
Photography is ubiquitous worldwide. We analyzed why people take, share, and use personal photographs, independent of their specific cultural background. These behaviors are still poorly understood. Experimental research on them is scarce. Smartphone technology and social media have pushed the success of photography, but cannot explain it, as not all smartphone features are widely used just because they are available. We analyzed properties of human nature that have made taking and using photographs functional behaviors. We did this based on the four levels, which Tinbergen (1963) suggested for analyzing why animals behave in a particular way. Including findings from multiple disciplines, we developed a novel conceptual framework—the “Mental Utilization Hypothesis of Photography.” It suggests that people adopt photography because it matches with core human mental mechanisms mainly from the social domain, and people use photography as a cognitive, primarily social coping strategy. Our framework comprises a range of testable predictions, provides a new theoretical basis for future empirical investigations into photography, and has practical implications. We conclude that photography has become a human universal, which is based on context-sensitive mental predispositions and differentiates itself in the social and societal environment.